PENGARUH SUKU BUNGA DAN INFLASI TERHADAP RETURN SAHAM PERUSAHAAN DI SEKTOR PERBANKAN YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2015-2017 - RIA FITRIA; ERIANDI ERIANDI; ALMIRA NANDA FEBRIYANI (BALANCING: Accountancy Journal, 2021)
Stock Return is a reward given to investors for the investment they have made. In this era, investment is an important activity in a country's economy, because investment can improve people's lives. Stock returns can inspire and attract investors to invest. The purpose of this study is to obtain empirical evidence about the effect of interest rates and inflation on stock returns. The population used is all banking companies listed on the Indonesia Stock Exchange in 2015-2017.